INTERNALIZATION OF TEACHER EDUCATION AS A PART OF A UNIVERSITY INTERNALIZATION STRATEGY - Lopukhova, Yulia; Makeeva, Elena; Kuzovenkova, Kseniya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The internationalization of University teacher education is very important today since teachers have to prepare students for living and working in the new global world. To prepare students for the globalization of the society, university teachers should have the opportunity to gain international experience – from traditional studies and internships to summer schools and degree theses abroad, blended learning formats, buddy programmes, international field trips to preparing English-language degree programmes together with international colleagues. In this paper the authors describe the IDUTE programme (International Dimension of University Teacher Education) designed to enhance the international dimensions of various components of University teacher education programmes, to transform courses in order to facilitate change and improvement in reaching the internationalization goals of their work and to help provide University teachers with greater global competence. This paper details the nature and specifics of the IDUTE programme and provides details of the programme’s outcomes and results. The authors have done extensive research to determine both the existing international content and programme practices for University teacher education and perceived needs for improvement. The IDUTE programme promotes internationalisation among technical teachers and students and expands intercultural competence into their studies and career through creation and development of separate 16/36/72-hour modules on international activities of University Teachers.